Educational Investment, Islamic Values, and Human Capital Formation A Maqāṣid-Based Framework for Contemporary Education - Deden Hidayat; Budiman Budiman; Noorma Yunia; Maskur Maskur (LP3M Pascasarjana STAI Ibnurusyd, 2026)
This study aims to develop a conceptual framework regarding the relationship between educational investment, Islamic values, and human capital formation through the maqāṣid al-syarī'ah approach. The research is motivated by the dominant Human Capital paradigm that views education as an economic investment to increase productivity and competitiveness, but has not yet comprehensively accommodated the spiritual, moral, and social dimensions. The study uses a qualitative approach with a library research type. Data analysis was conducted using content analysis techniques through the stages of data reduction, categorization, interpretation, and conceptual synthesis. The results show that maqāṣid al-syarī'ah is able to become an integrative paradigm in expanding the concept of educational investment through five main dimensions, namely ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-'aql, ḥifẓ al-nasl, and ḥifẓ al-māl. The integration of Human Capital theory and the maqāṣid al-syarī'ah (Islamic principles) produces the Maqāṣid-Based Human Capital Framework, which connects intellectual, spiritual, moral, social, and economic dimensions as indicators of holistic human capital development. This model provides a theoretical contribution to the development of Islamic education and serves as a conceptual foundation for formulating educational policies oriented toward productivity, character, welfare, and sustainable human resource development in the era of digital transformation.